Cells under siege: Viral glycoprotein interactions at the cell surface - Bowden, T; Jones, E; Stuart, D (2011)
As obligate parasites, viruses are required to enter and replicate within their host, a process which employs many of their proteins to hijack natural cellular processes. High resolution X-ray crystallographic analysis has proven to be an ideal method to visualize the mechanisms by which such virus-host interactions occur and has revealed the innovative capacity of viruses to adapt efficiently to their hosts. In this review, we draw upon recently elucidated paramyxovirus-, arenavirus-, and poxvirus-host protein complex crystal structures to reveal both the capacity of viruses to appropriate one component of a physiological protein-protein binding event (often modifying it to out-compete the host-protein), and the ability to utilize novel binding sites on host cell surface receptors. The structures discussed shed light on a number of biological processes ranging from viral entry to virulence and host antagonism. Drawn together they reveal the common strategies which viruses have evolved to interact with their natural host. The structures also support molecular level rationales for how viruses can be transmitted to unrelated organisms and thus pose severe health risks. © 2011 Elsevier Inc.